Impact of Alm on Indian Banks - Jessica, V Mary; Sireesha, N. (Ushus Journal of Business Management, 2021)
The basic function of commercial banks is Intermediation. In this process, banks undertake risks and reap rewards. In a regulated environment, the reward for intermediation is Net interest income, as banks accept deposits at regulated interest rates and lend at regulated rate and earn the interest spread.